Front pillar of the mandapa of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
A closer examination of the front pillar of the mandapa (pillared hall) reveals a male deity adorning its surface. Poised upon a lotus, he stands with a serene countenance and is depicted with two arms. In his right hand, he holds a dagger, while his left-hand lifts a bowl to his lips. Adorned with serpents as jewellery, these creatures coil around his neck, waist, and ankles, adding a mystical allure to his presence.